The Effect of Deep Placement of Basal Nitrogen Fertilizer on Gaseous Nitrogen Losses and Nitrogen Use Efficiency of Paddy Fields under Water-Saving Irrigation in Northeast China - Tiecheng Li; Zhongxue Zhang; Peng Chen; Zhijuan Qi; Tangzhe Nie; Zuohe Zhang; Di Sun; Sicheng Du; Xin Zhou (Agronomy, 2023)
As a widely implemented irrigation regime for paddy fields, water-saving irrigation (WSI) is capable of ensuring water resource security and improving nitrogen use efficiency (NUE). Higher gaseous nitrogen losses (GNL) lead to a low recovery rate of basal nitrogen, and this is the primary reason that restricts further improvements in the NUE under WSI. The deep placement of nitrogen fertilizer (DPN) is considered an efficient agricultural management measure to reduce GNL. However, the effects of WSI combined with the deep placement of basal nitrogen fertilizer on NUE, GNL, and rice yield in paddy fields remain largely unknown. In this study, a 2-year field experiment was conducted to measure GNL (N2O emissions and NH3 volatilization), NUE, and rice yield. Four treatments were utilized: (i) conventional flooding irrigation + broadcast of nitrogen fertilizer (110 kg N hm−2, CFN); (ii) water-saving irrigation + deep placement of basal nitrogen fertilizer (110 kg N hm−2, WSN); (iii) water-saving irrigation + deep placement of basal nitrogen fertilizer (99 kg N hm−2, WSN1); (iv) water-saving irrigation + deep placement of basal nitrogen fertilizer (88 kg N hm−2, WSN2). The results showed that the GNL in paddy fields under treatment ranged from 5.29 to 10.67 kg hm−2. Deep placement of basal nitrogen fertilizer mitigated the GNL of the paddy fields under WSI. The GNL of CFN was significantly higher than those of WSN1 and WSN2 by 26.9% and 54.0% in 2021 and 14.4% and 23.3% in 2022, respectively (p < 0.05). Under WSI, the deep placement of basal nitrogen fertilizer reduced the GNL primarily via the reduction of NH3 volatilization. NH3-N of CFN was higher than those treatments under WSI. The rice yield of CFN was significantly lower than those of WSN and WSN1 by 22.4% and 21.6% in 2021 and 4.6% and 1.5% in 2022, respectively. (p < 0.05). Moreover, the NUE of each treatment under WSI was higher than that of CFN. These changes exhibited similar trends in 2021 and 2022. These results demonstrated that deep placement of basal nitrogen fertilizer is an effective practice to ensure food and environmental security under WSI.